ANALISIS SPASIAL INDUSTRI KECIL DAN MENENGAH DI PROPINSI NUSA TENGGARA TIMUR - Arifin, Zainal (Jurnal Ekonomi Pembangunan, 2011)
This study aims to identify patterns of spatial concentration of Small and Medium Enterprises in East Nusa Tenggara judging by the amount of labor and production as well as the factors that affect the employment period 2005-2009. Analysis tools used include: Spatial Analysis, Geographic Information Systems, and multiple linear regression. This study found that the distribution of Small and Medium Enterprises in East Nusa Tenggara is not evenly distributed geographically, when viewed from the employment and production quantities. In some  counties and cities experienced employment and production quantities are high, while some others were experiencing employment and production quantities are low. It also reinforced the results of multiple linear regression analysis with panel data with the result that all explanatory variables X1 (business units), X2 (investment), X3 (production) and X4 (raw materials) are able to explain to the employment of Small and Medium Industries in East Nusa Tenggara.